Fostering path to a just culture in healthcare organizations: Influential factors and challenges - Ongko, Tjindrawati; Chalidyanto, Djazuly (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2023)
Patient safety culture is paramount in healthcare, and fostering a just culture is essential for promoting incident reporting as a means of collective learning rather than blame. This study aims to understand the process of establishing a just culture in healthcare organizations, its influencing factors, and associated challenges. Following PRISMA 2020 guidelines, a systematic search of electronic databases from 2019 to 2023 was conducted. The focus was on quantitative, qualitative, and mixed-method studies exploring just culture, patient safety, healthcare organizations, influencing factors, and challenges. STROBE criteria were used for quality assessment, and data extraction included authors, publication year, participants, interventions, and outcomes. To establish a just culture emphasizing accountability and transparency, distinguishing human errors from risky or reckless behaviors is crucial. Building a just culture encourages error reporting while maintaining a balance between a blame-free and punitive environment. Key influencing factors include organizational characteristics (safety climate and just culture) and personal factors (patient safety knowledge), particularly among nurses. The challenges faced include privacy-protecting policies that may hinder open communication and trust factors, as emotional consequences can arise from safety incidents. Fostering a just culture is vital for enhancing patient safety. Five influential factors emerged: Awareness, Empowerment, Organizational Factors, Leadership, and Communication. Challenges include privacy-protecting policies hindering open communication and trust issues, potentially leading to emotional consequences from safety incidents. Further research is needed to explore implementation processes and assess their impact on patient safety culture, incident reporting, system improvements, and responsible behaviors in healthcare organizations